Embryological evidence substantiates the subcoxal theory on the origin of pleuron in insects - Yuta Mashimo (Nature Portfolio, 2017)
Abstract The lateral body plate pleuron is a significant structure in insects that contributes to the development and elaboration of wings and limbs (appendages). Although the pleuron is thought to originate from the proximal-most appendicular segment, the subcoxa, details remain unclear, and the morphological boundary between the dorsal body plate tergum and appendage (BTA) has not been clearly specified. Employing low-vacuum scanning electron microscopy (SEM) and the nano-suit method for SEM, we followed, in detail, the development of the thoracic segments of the two-spotted cricket Gryllus bimaculatus and succeeded in clearly defining the BTA. This study demonstrates the subcoxal origin of the pleuron, suggests the tergal origin of spiracles, and reveals that the wing proper originates exclusively from the tergum, whereas the wing hinge and direct muscles may be appendicular in origin, suggesting the dual origin (i.e., tergal plus appendicular origin) of wings.